Manufacturing Magic and Computational Creativity - Williams, Howard; McOwan, Peter W. (Frontiers in Psychology, 2016)
This paper describes techniques in computational creativity, blending mathematical modelling and psychological insight, to generate new magic tricks. The details of an explicit computational framework capable of creating new magic tricks are summarised, and evaluated against a range of contemporary theories about what constitutes a creative system. To allow further development of the proposed system we situate this approach to the generation of magic in the wider context of other areas of application in computational creativity in performance arts. We show how approaches in these domains could be incorporated to enhance future magic generation systems, and critically review possible future applications of such magic generating computers.